The transcription factor Ste12-like increases the mycelial abiotic stress tolerance and regulates the fruiting body development of Flammulina filiformis - Lyu, Xiaomeng; Wang, Qingji; Liu, Ao; Liu, Fang; Meng, Li; Wang, Panmeng; Zhang, Yan; Wang, Li; Li, Zhuang; Wang, Wei (Frontiers in Microbiology, 2023)
Flammulina filiformis is one of the most commercially important edible fungi worldwide, with its nutritional value and medicinal properties. It becomes a good model species to study the tolerance of abiotic stress during mycelia growth in edible mushroom cultivation. Transcription factor Ste12 has been reported to be involved in the regulation of stress tolerance and sexual reproduction in fungi. In this study, four ste12-like overexpression transformants of F. filiformis were constructed by Agrobacterium tumefaciens-mediated transformation. All the overexpression transformants were more tolerant to salt stress, cold stress and oxidative stress than wild-type strains. In the fruiting experiment, the number of fruiting bodies of overexpression transformants increased compared with wild-type strains, but the growth rate of stipes slowed down. It suggested that gene ste12-like was involved in the regulation of abiotic stress tolerance and fruiting body development in F. filiformis.